Effect of Limb Lengthening on Internodal Length and Conduction Velocity of Peripheral Nerve - Simpson, A. Hamish (J Neurosci, 2013)
The influences of axon diameter, myelin thickness, and internodal length on the velocity of conduction of peripheral nerve action potentials are unclear. Previous studies have demonstrated a strong dependence of conduction velocity on internodal length. However, a theoretical analysis has suggested that this relationship may be lost above a nodal separation of ∼0.6 mm. Here we measured nerve conduction velocities in a rabbit model of limb lengthening that produced compensatory increases in peripheral nerve growth. Divided tibial bones in one hindlimb were gradually lengthened at 0.7 mm per day using an external frame attached to the bone. This was associated with a significant increase (33%) of internodal length (0.95–1.3 mm) in axons of the tibial nerve that varied in proportion to the mechanical strain in the nerve of the lengthened limb. Axonal diameter, myelin thickness, and g-ratios were not significantly altered by limb lengthening. Despite the substantial increase in internodal length, no significant change was detected in conduction velocity (∼43 m/s) measured either in vivo or in isolated tibial nerves. The results demonstrate that the internode remains plastic in the adult but that increases in internodal length of myelinated adult nerve axons do not result in either deficiency or proportionate increases in their conduction velocity and support the view that the internodal lengths of nerves reach a plateau beyond which their conduction velocities are no longer sensitive to increases in internodal length.